ChemInform Abstract: Efficient and Green Syntheses of 12‐Aryl‐2, 3, 4, 12‐tetrahydrobenzo[b]xanthene‐1, 6, 11‐triones in Water and Task‐Specific Ionic Liquid. Issue 43 (7th October 2013) - Khurana, Jitender M.; Lumb, Anshika; Chaudhary, Ankita; Nand, Bhaskara
Abstract A convenient one‐pot cascade/tandem method for the synthesis of the title compounds under extremely mild reaction conditions is reported.